Velocidad de forrajeo y área foliar transportada por la hormiga Acromyrmex subterraneus (Hymenoptera: Formicidae - Gomides, Cecília H.F (Universidad de Costa Rica, 1997)
Although leaf-cutting ants are considered to be an important pest in agriculture and forestry in South America, several aspects of their ecology are still unknówn. Foraging speed of Acromyrmex' su.bterraneus· ;subterraneus and relationshipbetween size of forager aild load werestudied in Vicosa, Brazil. Time spent by wRorkers. (Ie\lving :the nest or returning to it, loaded or unloaded), to qoss a 40 cm space from nest entrance wás mea,This speed. This'speed was dete,n:nined twice ead) ínónth, every hour from begillning of foraging to its end, during 12coÍlsecutivemonths.TwelltY wóikers áÍldtheii loads weresecurM al fiveoccasions fot measurement. Mean speed varied fn!m 0.5 'to L2 mlh).in; lower valUes )Vete, found durí,ng Winter time. Worker,s,leaving the nest Were faster (0.93mfmin) than loaded workers (0.78 mlmin).,No relatioln shil? could be found between worker silíes and load size.,